Hemodynamic changes during off-pump versus on-pump cardiac surgeries - Siddique, Abul B. M.; Taher, Abu; Moral, M. Salim; Ahmed, Mohammed S.; Alam, M. Hassnul; Harun-Ur-Rashid , M. (International Journal of Advances in Medicine, 2025)
Background: Coronary artery bypass grafting (CABG) is a vital procedure for treating coronary artery disease (CAD). Traditionally, CABG is performed with cardiopulmonary bypass (CPB), known as on-pump surgery, which can cause complications like systemic inflammatory response and organ dysfunction. The primary objective of this study was to compare the hemodynamic changes during off-pump and on-pump cardiac surgeries, focusing on heart rate, blood pressure, and other key intraoperative and postoperative parameters. Methods: This prospective observational study at BSMMU (2021-2022) compared hemodynamic changes in 160 patients undergoing on-pump and off-pump cardiac surgeries. Data were collected preoperatively, intraoperatively, and postoperatively in the intensive care unit (ICU). Statistical analysis was performed using statistical package for the social sciences (SPSS), with t-tests and Chi-square tests applied for comparisons. Results: The study compared 160 patients (80 on-pump, 80 off-pump). The off-pump group had a lower heart rate (72±8 versus 75±10 beats/min, p=0.045) and higher mean arterial pressure (88±11 versus 85±12 mmHg, p=0.032). ICU stay was shorter in the off-pump group (2.8±1.0 versus 3.5±1.2 days, p=0.027), as was total hospital stay (6.5±1.8 versus 8.5±2.3 days, p=0.015). Thirty-day mortality was 3.8% for on-pump and 2.5% for off-pump (p=0.112), with one-year mortality at 6.3% versus 3.8% (p=0.089). Conclusions: This study demonstrates that off-pump cardiac surgery results in improved hemodynamic stability, reflected in lower heart rates and higher mean arterial pressure during surgery compared to on-pump surgery.